Microwave Scissors-Based Sutureless Laparoscopic Partial Nephrectomy Versus Conventional Open Partial Nephrectomy in a Porcine Model: Usefulness and Complications - Nguyen, Ha Ngoc; Yamada, Atsushi; Naka, Shigeyuki; Murakami, Koichiro; Tani, Soichiro; Tani, Tohru (Annals of Surgical Oncology, 2024)
Background This study aimed to compare the benefits and safety of microwave scissors-based sutureless laparoscopic partial nephrectomy (MSLPN) with those of conventional open partial nephrectomy (cOPN). Methods Each kidney in nine pigs underwent MSLPN using microwave scissors (MWS) via transperitoneal laparoscopy or cOPN via retroperitoneal open laparotomy. The kidney’s lower and upper poles were resected under temporary hilar-clamping. The renal calyces exposed during renal resections were sealed and transected using MWS in MSLPN and were sutured in cOPN. For MWS, the generator’s power output was 60 W. Data on procedure time (PT), ischemic time (IT), blood loss (BL), normal nephron loss (NNL), and extravasation during retrograde pyelogram were compared between the two techniques. Results The authors successfully performed 22 MSLPNs and 10 cOPNs. Compared with cOPN, MSLPN was associated with significantly lower PT (median, 9.2 vs 13.0 min; p = 0.026), IT (median, 5.9 vs 9.0 min; p < 0.001), BL (median, 14.4 vs 38.3 mL; p = 0.043), and NNL (median, 7.6 vs 9.4 mm; p = 0.004). However, the extravasation rate was higher in the MSLPN group than in the cOPN group (54.5 % [ n = 12] vs 30.0 % [ n = 3]), albeit without a significant difference ( p = 0.265). Pelvic stenosis occurred in one MSLPN procedure that involved deep lower pole resection near the kidney hilum. Conclusions The study data show that MSLPN can improve intraoperative outcomes while reducing technical demands for selected patients with non-hilar-localized renal tumors. However, renal calyces, if violated, should be additionally sutured to prevent urine leakage.